Perinatal Management in a Pregnant Woman with Ureteropelvic Junction Obstruction: Case Report and Literature Review - Daisuke Tamura; Shintaro Narita; Misa Yamauchi; Rina Watanabe; Shota Yokoyama; Akane Kikuchi; Akihiro Shitara; Syuji Chiba; Fumiko Saito; Akihiro Sugita; Kazunari Sato; Akihiro Karube (Diagnostics, 2022)
Although giant hydronephrosis (GH) associated with ureteropelvic junction obstruction (UPJO) is extremely rarely detected in pregnant women, diagnostic methods, therapeutic approaches, and perinatal management have not been established. A 31-year-old Japanese primipara had a 15 cm × 12 cm multi-cystic mass in the right abdomen detected by transabdominal ultrasound at gestational week 26. Magnetic resonance imaging revealed that the mass was right renal GH. She underwent serial ultrasound-guided transretroperitoneal drainage as conservative treatment. She delivered vaginally at gestational week 36. Since she had flank pain and a documented non-functional right kidney, laparoscopic nephrectomy was conducted 22 months after delivery. UPJO with fewer smooth muscle cells and fibrosis was histologically diagnosed in the surgical specimen. Her postpartum and postoperative courses were uneventful for 10 months. We performed a literature review of diagnostic methods, clinical characteristics, and perinatal management in pregnant women with GH due to UPJO.